Strong support for a heterogeneous speciation decline model in Dinosauria: a response to claims made by Bonsor et al. (2020). Issue 8 (25th August 2021) - Sakamoto, Manabu; Benton, Michael J.; Venditti, Chris
Abstract : Through phylogenetic modelling, we previously presented strong support for diversification decline in the three major subclades of dinosaurs (Sakamoto et al . 2016 Proc. Natl Acad. Sci. USA 113, 5036–5040. (doi:10.1073/pnas.1521478113 )). Recently, our support for this model has been criticized (Bonsor et al . 2020 R. Soc. Open Sci. 7, 201195. (doi:10.1098/rsos.201195 )). Here, we highlight that these criticisms seem to largely stem from a misunderstanding of our study: contrary to Bonsor et al .'s claims, our model accounts for heterogeneity in diversification dynamics, was selected based on deviance information criterion (DIC) scores (not parameter significance), and intercepts were estimated to account for uncertainties in the root age of the phylogenetic tree. We also demonstrate that their new analyses are not comparable to our models: they fit simple, Dinosauria-wide models as a direct comparison to our group-wise models, and their additional trees are subclades that are limited in taxonomic coverage and temporal span, i.e. severely affected by incomplete sampling. We further present results of new analyses on larger, better-sampled trees ( N = 961) of dinosaurs, showing support for the time-quadratic model. Disagreements in how we interpret modelled diversification dynamics are to be expected, but criticisms should be based on sound logic and understanding of the model under discussion.